EMPOWERMENT OF CASH WAQF FOR IMPROVING PUBLIC HEALTH - Faisal Faisal; Syarifah Citra Meidina (Proceeding International Seminar of Islamic Studies, 2022)
The conditions of many people nowdays is experiencing a slump, especially in finance field. This has an impact on public health conditions, namely the presence of people who are sick, unable to buy drugs or cannot meet their health care costs. To help and improve public health, it is necessary to empowerment cash waqf for people who cannot afford it.The research is normative juridical research. The data sources in this research is secondary data. The technique to collecting data is documentation study.Based on the research discovered that the empowerment of waqf can be done by distributing cash waqf to members of the unable community who are in a sick condition. The provision of cash waqf aims so that they can buy drugs or vitamins needed for health, as well as for the cost of treatment. So that the sick people can recover without having to think about the cost of treatment.Keywords: Empowerment, cash waqf, public health